Identifikasi Keberadaan Mikroplastik Pada Saluran Pencernaan Ikan Amoy (Lutjanus Vitta) Di Pulau Numbing Kabupaten Bintan - Febbiyana, Della; Simbolon, Veronika Amelia; Daswito, Rinaldi (Jurnal Kesehatan Lingkungan Mapaccing, 2026)
Microplastic pollution poses a serious threat to the environment and human health. As the world's second-largest plastic waste contributor, Indonesia significantly adds to high microplastic levels in its waters. Amoy fish are at high risk of exposure due to their coral reef habitat. This study aimed to identify the presence of microplastics in the digestive tracts of Amoy fish (Lutjanus vitta) obtained from fishermen's catches in the waters of Numbing Island, Bintan Regency. This was a descriptive observational study that used a sample of 30 Amoy fish. The research was conducted from January to June 2025. Microplastic identification was performed using the NOAA (National Oceanic and Atmospheric Administration) method with the addition of H2O2 and FeSO4, and data were analyzed univariately. The results showed that microplastics were found in all 30 fish samples examined, with a total of 183 particles and an average abundance of 6.1 particles per fish. The dominant microplastic shapes were fibers (85.24%), followed by fragments (9.28%) and films (5.46%). In conclusion, microplastics were present in all fish samples, with fibers being the most common shape and an abundance of 6.1 particles per fish. It is recommended that the community independently manages household waste to prevent plastic from entering the sea and adopts habits of sorting and recycling waste. The Environmental Agency is expected to supervise plastic waste management and educate the public on the dangers of microplastics.